551. Convalescent plasma early in disease course improves survival in COVID-19. (31st December 2020) - Nauriyal, Varidhi; Shallal, Anita; Vahia, Amit T; Samuel, Linoj; Tibbetts, Robert; Lopez-Plaza, Ileana; Ramesh, Mayur
Abstract: Background: Convalescent plasma (CP) has been described as a potential therapy for coronavirus disease 2019 (COVID-19). Given paucity of data, we sought to describe characteristics of CP recipients in survivors and non-survivors. Methods: We conducted retrospective review of electronic medical records which included any patient with a positive SARS-CoV-2 PCR test who received CP at an 890-bed quaternary care hospital in Southeast Michigan between March-May 2020. Data collected included: demographics, co-morbidities, mSOFA score on admission, laboratory values, and treatment. Outcomes assessed included inflammatory markers and clinical status based on an 8-point ordinal scale a . These values were recorded on admission, the date of CP (day 1), day 3, 7, and day 30 post-CP. Patient outcomes were stratified by ordinal scale score and compared using Mann-Whitney U tests to examine differences in clinical characteristics: scale of 1–4 ("meaningful survivor"), 5–7 ("survivor"), and 8 ("non-survivor"). Results: Results of our study are summarized in Table 1 and 2. Non-survivors were older than survivors (62 vs 71 years; p=0.026). There was no statistically significant difference between patient gender, race, number of days from positive PCR test to CP, treatments, and co-morbidities. There was a trend toward higher mSOFA score on admission in non-survivors (p=0.056). A lower ordinal scale score on the date of receiving CP was significantly associated with meaningful survivorship (6 vs 7, p=0.005). Comparisons of Characteristics Based on Ordinal Scale at Day 30 Comparisons of Outcomes Based on Ordinal Scale at Day 30 Conclusion: Patients who have a lower ordinal scale score on the date of CP administration are most likely to have meaningful survivorship at day 30. Future studies should evaluate optimal timing and outcomes for CP therapy in COVID-19. Disclosures: All Authors : No reported disclosures